A randomized controlled trial to test the efficacy of trans-tympanic injections of a sodium thiosulfate gel to prevent cisplatin-induced ototoxicity in patients with head and neck cancer - Viannique Rolland; François Meyer; Matthieu J. Guitton; Richard Bussières; Daniel Philippon; Isabelle Bairati; Mathieu Leclerc; Mathieu Côté (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Cisplatin-induced hearing loss is frequent and severe. Antioxidants such as sodium thiosulfate (STS) can neutralize the effects of cisplatin. The objective of the trial was to test the efficacy of trans-tympanic injections of a STS gel to prevent cisplatin-induced ototoxicity. Methods Eligible participants were newly diagnosed patients with stage III or IV squamous cell carcinoma of the mouth, oropharynx, hypopharynx, or larynx and scheduled to be treated by concurrent chemoradiation (CCR). Patients with asymmetric hearing were not eligible. The planed treatment included cisplatin 100 mg/m2 at days 1, 22 and 43. A baseline pre-treatment complete audiometric evaluation (pure tone at frequencies ranging from 0.5 to 14 kHz, bone conduction at 0.5–4 kHz and DPOAEs) was performed. Adverse effects were noted according to CTCAE. On the day before the beginning of CCR, eligible and consenting patients were randomized to receive a trans-tympanic injection of the gel either in the left ear or in the right ear. A final post-treatment complete audiometric evaluation was scheduled to be performed 1 month after the end of CCR by audiologists kept blind to the ear assignment. For the main outcome, the permanent threshold shift (PTS) in decibel (dB) was calculated as the difference between the final and baseline measures at all pure tone frequencies at 0.5–14 kHz for each patient and for each ear. The main outcome was assessed blindly in a mixed linear model with the PTS as the dependent variable and intervention, frequency, their interaction and radiation dose to the cochlea as independent variables. Results Between January 2015 and April 2016, 13 patients were randomized. The trial was stopped in June 2016 for poor accrual. The average loss of hearing over all frequencies was 1.3 dB less for treated ears compared to control ears. Although not statistically (p = 0.61) nor clinically significant, the difference was in favor of the treated ears for all frequencies between 3 and 10 kHz. Conclusions Our trial suggests that STS deposited on the round window was safe for the middle and inner ears. More work is needed to improve the efficacy of trans-tympanic injections of cisplatin antidotes. Trial registration ClinicalTrials.gov, NTC02281006, Registered 3 November 2014.